IbM USAHA TEMPE DI DESA JURANGSAPI KECAMATAN TAPEN KABUPATEN BONDOWOSO - Wendy Triadji Nugroho; Naning Retnowati (Publisher UPT P2M Politeknik Negeri Malang, 2019)
Science and technology activities for the Society (IbM) aims to help entrepreneurs micro tempe that a lack of adequate production capacity, business management and marketing distribution. Therefore we need a more modern equipment and training managerial and marketing efforts to increase production capacity and broaden the partners in order to manage their business better so that its revenue increased. After obtaining aid equipment comprising of several means of production and production support, the volume increased soybean production partner and marketing area can be expanded even if it is still around regency.